Finding common ground: developing a shared understanding of tropical peatswamp forest restoration and fires across culture, language, and discipline. (1st September 2022) - Rawluk, A.; Sanders, A.; Yuwati, T.W.; Rachmanadi, D.; Izazaya, N.; Yulianti, N.; Sakuntaladewi, N.; Dyson, A.; Graham, L.; Kunarso, A.; Damanik, Z.; Farquharson, R.; et al.
Indigenous and traditional peoples, practitioners and researchers navigate complex social ecological landscapes. The importance of dialogue across cultures, languages, disciplines, and forms of knowledge is increasingly recognised as needed in landscape restoration and environmental governance at multiple scales. A process called adaptive doing was used in two workshops in South Kalimantan Province, followed by remote collaboration among team members in Indonesia and Australia. Examining the breadth of differences in culture, language and knowledge, and recognising assumptions and disciplinary training, enabled each participant to develop a shared understanding of tropical peatswamp forest restoration and fires. The shared understanding extended beyond each participant's original conception and provided a collective vision that brought together the different knowledges, cultural and disciplinary backgrounds, while acting as a point of orientation for the work and purpose within a research project. The experience gained through adaptive doing has led to important collaborative changes in the project and can support future interdisciplinary teams to achieve collaborative practice change and a shared understanding of context.